2021
DOI: 10.1096/fj.202001653rr
|View full text |Cite
|
Sign up to set email alerts
|

Pathological mechanisms of vacuolar aggregate myopathy arising from a Casq1 mutation

Abstract: Vacuolar aggregate myopathy (VAM, OMIM# 616231) is a rare human muscle disorder, linked to mutations in CASQ1 and presents with elevated serum creatine kinase, fatigue, myalgia, muscle cramps, lower limb hypertrophy, and muscle weakness. [1][2][3][4] Muscles from VAM patients frequently contain protein aggregates and an increased number of vacuoles. [1][2][3][4] Mutation of a conserved aspartic acid at position D244 to glycine (D244G, DG) in CASQ1 associated with VAM in humans slows sarcoplasmic reticulum (SR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
(199 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, three DE-ERSRGs in our results showed a trend of downregulation in response to psychological stress and upregulation after treatment. Among them, Tfrc and Casq1 usually play a protective role and lead to the generation of ER stress when external factors cause their lowering ( Jung et al, 2015 ; Hanna et al, 2021 ), which is also consistent with our results. Payne et al suggested that Nos2 could protect against the development of ER stress ( Payne et al, 2001 ), whereas in other studies, increased Nos2 expression has been suggested to exacerbate ER stress ( Deslauriers et al, 2011 ; Zanotto et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, three DE-ERSRGs in our results showed a trend of downregulation in response to psychological stress and upregulation after treatment. Among them, Tfrc and Casq1 usually play a protective role and lead to the generation of ER stress when external factors cause their lowering ( Jung et al, 2015 ; Hanna et al, 2021 ), which is also consistent with our results. Payne et al suggested that Nos2 could protect against the development of ER stress ( Payne et al, 2001 ), whereas in other studies, increased Nos2 expression has been suggested to exacerbate ER stress ( Deslauriers et al, 2011 ; Zanotto et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%